(untitled) - Enger, Eldon D. (Boston, Mass, 2000)
This book is organized to provide an even, logical flow of concepts and to provide clear illustrations of the major environmental issues of today as interrelatedness; ecological principles and their application; energy; human influences on ecosystems; and pollution and policy
Keywords: Environmental sciences,Environmental protection